1-Arylsulfonyl-2-(Pyridylmethylsulfinyl) Benzimidazoles as New Proton Pump Inhibitor Prodrugs - Young-moon Cho; Michael Garst; Jai Moo Shin; George Sachs (Molecules, 2009)
New arylsulfonyl proton pump inhibitor (PPI) prodrug forms were synthesized. These prodrugs provided longer residence time of an effective PPI plasma concentration, resulting in better gastric acid inhibition.